MOROCCAN-SPANISH COUPLES’ DECOLONIAL RESPONSES ON TIKTOK - Civila, Sabina; Jaramillo-Dent, Daniela (AoIR Selected Papers of Internet Research, 2023)
In the past years, the use of social media has allowed migrants and other minority groups to communicate, obtain information and build an identity through self-representation and content creation. The possibility to talk about their experiences, connect to other content creators and interact with the platform allows to decentralize the European narrative and offer visibility to other cultures. In this context, TikTok emerges as one of the platforms where traditionally marginalized populations narrate their experiences and enter public debates. In this case we study Spanish-Moroccan mixed couples who must face the cultural stereotypes derived from the geographical, historical, and colonial confluences between these two nations. To carry out the study, a qualitative analysis was carried out by identifying TikTok videos using the hashtags #mixedcouples and #SpainandMorocco in their Spanish and English versions. We then identified other hashtags of interest that appeared together with these and found other videos of interest. We viewed a total of 8,653 videos and identified six profiles of interest from creators that self-identified as being part of a Spanish-Moroccan mixed couple and had more than 10K followers. This analysis reflects the difficulties faced by people who chose more intimate forms of integration and the existing colonial paradigms in terms of mixed romantic partners. At the same time, these creators exemplify the existence of points of encounter between seemingly opposite cultures and nationalities through their (self)representations and discourses on this platform, as well as the increased visibility they are achieving through their content and profiles.